The Prevalence of Renal Scars Among Infants Under One Year Old With a First UTI With or Without VUR in Qom, Iran, 2017 (Iranian Journal of Kidney Diseases, 2020)
Renal scarring with reflux develops renal nephropathy. The risk is higher when it is associated with urinary tract infection (UTI). Hence, we investigated the prevalence of renal scars among children under one-year-old with the first UTI in Qom, Iran. We conducted this retrospective study on 140 infants divided in two reflux (n = 70) and non-reflux (n = 70) groups. Participant’s records had been analyzed by descriptive and analytic statistics. The prevalence of renal scar was 32.12% among all 140 infants. The prevalence of renal scars among children with and without reflux, was 33 (47.1%), and 12 (17.1%) out of 70 (P < .001); respectively. The rate of renal defects increased with higher grades of reflux. We found that the rate of renal scar is high in Qom. Therefore, we recommend screening susceptible children in order to prevent renal damage.